Космічні радіоелектронні системи - Вовченко, А. Р. (ХНУРЕ, 2025)
The development of space-based radio-electronic systems has significantly enhanced modern communication, navigation, and surveillance technologies. These systems play a crucial role in satellite telecommunications, deep space exploration, Earth monitoring, and military applications. The integration of advanced signal processing, artificial intelligence, and quantum communication ensures improved reliability and security of space systems. This study explores the latest advancements in space radio-electronic technologies, highlighting their applications, challenges, and future dirctions
Keywords: космічні радіоелектронні системи; space-based radio-electronic systems